Consequences of Loss of an Abundant Pollinator: An Experimental Study - (:unkn) unknown (My University, 2016)
Pollinator populations are declining worldwide, and this may lower the quantity and quality of pollination services. Since pollinators often compete for floral resources, loss of an abundant pollinator species may release others from competition and potentially alter floral visitation rates. We explored how the removal of a frequent pollinator, bumble bees, influenced pollination success of whorled milkweed (Asclepias verticillata). In three small and three large populations we quantified pollinator visitation rates and pollination success for control plots and for plots where bumble bees were experimentally excluded. We found that exclusion of bumble bees did not reduce A. verticillata pollination success. Visitation by Polistes wasps increased markedly (293%) following bumble bee exclusion, especially in large populations (400%). Because Polistes wasps were just as efficient as bumble bees at pollen transport, increased wasp visitation offset lost bumble bee pollination services. This study provides a vivid example of the challenges associated with forecasting how pollinator declines may influence pollination success. When pollinator loss is followed by a shift in the composition of visiting pollinator species, implications for pollination success will depend on the net change in the quantity and quality of pollination services.
Keywords: Asclepias Verticillata; Bombus Griseocollis; Plant-Pollinator Interactions; Pollination; Pollinator Competition; Pollinator Effectiveness